Scavenger endothelial cells of fish, a review. Issue 9 (17th May 2021) - Seternes, Tore; Bøgwald, Jarl; Dalmo, Roy A.
Abstract: The definition of scavenger endothelial cells (SEC) is exclusively based on functional and structural characteristics. The following characteristics are common hallmarks for the vertebrate SEC: (a) All vertebrates examined are furnished with a population of special SEC that plays a role in the catabolism of physiologic and non‐physiologic soluble waste macromolecules. (b) From the ligands that are endocytosed, SEC in all seven vertebrate classes appear to express the collagen α‐chain receptor and the scavenger receptors. In addition, the hyaluronan and the mannose receptors are present on SEC of mammalia (several species) and osteichthyes (e.g., salmon and cod). It is likely that all four receptor types are present in all vertebrate classes. (c) Like liver endothelial cells (LEC) in mammals, SEC in all vertebrate classes are geared to endocytosis of soluble macromolecules, but phagocytic uptake of particles is taken care of mainly by macrophages. (d) The most primitive vertebrates (hagfish, lamprey and ray) carry their SEC in gill vessels, whereas phylogenetically younger fishes (salmon, carp, cod and plaice) carry their SEC in either kidney or heart and in all terrestrial vertebrates—SEC are found exclusively in the liver. (e) SEC of all vertebrates are localized in blood sinusoids or trabeculae that carry large amounts of slowly flowing and O2 poor blood. (f) SEC differs functionally and structurally from what is normally associated with "conventional vascular endothelium."